Using SiO2 nano-particles for better color uniformity and lumen output in 8500 K conformal and in-cup white LEDs - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Thuc Minh Bui; Tri-Vien Vu (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In the effort of improving the performance of white light LEDs devices (WLEDs), the SiO2 nano-particles were applied and have shown a significant impact on the optical properties. Specifically, the light output of the lighting devices is enhanced when a mixture of SiO2 particles and silicone gel is diffused on the encapsulation layer surface. This enhancement is the result of light scattering from SiO2 that strengthens the emitted blue light at further angles and reduces the color discrepancy. The evidence is that CCT deviation in SiO2-doped structure decline from 1000 K to 420 K in -70° to 70°. In addition, the SiO2 with refractive index in between the phosphor material and outside environment allows light to be emitted outward more effectively. This lighting enhancement of SiO2-doped structure increases the lumen output by 2.25% at 120 mA power source in comparison to structure without SiO2. These experimental outcomes suggest that SiO2 is an effective material to add in WLEDs structure for better lighting efficiency.